2021
DOI: 10.1175/jcli-d-21-0112.1
|View full text |Cite
|
Sign up to set email alerts
|

A continuous decline of global seasonal wind speed range over land since 1980

Abstract: To investigate changes in global wind speed phenomena, we constructed homogenized monthly time series (1980-2018) for 4,722 meteorological stations. Through examining monthly-averaged wind speeds (MWS), we found that seasonal wind speed range (SWSR; calculated as the difference between maximum and minimum MWS) has declined significantly by 10% since 1980 (p < 0.001). This global SWSR reduction was primarily influenced by decreases in Europe (-19%), South America (-16%), Australia (-14%), and Asia (-13%), wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 83 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Wind energy potential in winter under SSP2-4.5 and SSP5-8.5 shows an increasing trend in most areas for 2031–2060 (Figure S9e, f), while the opposite case occurs in summer (Figure S9h, i). Such distinct seasonal features may be attributed to the seasonal variations of monsoons and ocean currents. Northern and western China stations, identified by K-means clustering, show a significant decreasing trend (see Text S5, Table S6, and Figure S10 for details). This suggests that wind energy resources in some parts of China may decrease and become more variable on an inter- and intra-annual basis due to climate change.…”
Section: Resultsmentioning
confidence: 99%
“…Wind energy potential in winter under SSP2-4.5 and SSP5-8.5 shows an increasing trend in most areas for 2031–2060 (Figure S9e, f), while the opposite case occurs in summer (Figure S9h, i). Such distinct seasonal features may be attributed to the seasonal variations of monsoons and ocean currents. Northern and western China stations, identified by K-means clustering, show a significant decreasing trend (see Text S5, Table S6, and Figure S10 for details). This suggests that wind energy resources in some parts of China may decrease and become more variable on an inter- and intra-annual basis due to climate change.…”
Section: Resultsmentioning
confidence: 99%
“…The annual and seasonal mean wind speed is at a low level globally recently, as many previous research have suggested. [18][19][20][21] In terms of wind speed variability, only Zhou et al 67 have noted that the seasonal wind speed range has decreased significantly globally since 1980, indicating a decline in wind speed variability. These findings suggest that in recent years, the global wind speed also has had a weak mean state and variability.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The reason for recently observed changes in wind velocities in the last decade is still unknown, but they are potentially linked with large-scale synoptic climate forcing (e.g., ENSO, Arctic Oscillation, Pacic Decadal Oscillation, midlatitude westerlies) that may change on decadal time scales. 28,29 While rehabilitation will play a positive role in mitigating sand-dust storm generation by increasing vegetation ground cover in part of the source area, 14,17,18 rehabilitation efforts may require ne tuning to be most effective. Further investigation is needed regarding the co-location of areas experiencing wind speed changes and exceptionally dry conditions.…”
Section: Discussionmentioning
confidence: 99%